PENGARUH MUROTTAL TERHADAP PENURUNAN TINGKAT NYERI IBU BERSALIN KALA I FASE AKTIF DI RSUD dr. ZAINOEL ABIDIN - Wirna Hildayati; Siti Hasanah; Evi Kurniawati (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2021)
Labor pain can cause hyperventilation. This situation will stimulate an increase in catecholamines which can cause obstruction in the strength of uterine contractions such as uterine inertia. The condition can cause fetal distress and maternal death during childbirth. Monitoring and intervention of labor pain in the first stage, especially in the active phase is very important, because it determines whether a mother can undergo a normal delivery or must given an intervention because of severe pain. One of the distraction techniques that can be used is murottal Al-Qur'an. Distraction is an act of diverting the pain experienced by doing something else. One of them is listening to murottal Al-Qur'an. The purpose of the research is to describe the effect of murottal on reducing the level of maternal pain during the active phase of the first stage of labor in dr. Zainoel Abidin hospital. This research is a quantitative research, where the research design used is Quasi Experimental Design with One Group Pretest-Postest. The population is all mothers who give birth during the Active phase of first stage totaling 30 people. In this study, before the intervention the average pain scale was 3.00 with standar deviation of 0.830. After the intervention the average pain scale was 1.67 with standar deviation of 0.547 with an average difference of 1.33. The result show that murrotal has significantly effect on reducing the level of maternal pain in the active phase of first stage at dr. Zainoel Abidin hospital with p-value 0.001. the conclusion is it was suggested to midwife apply murottal al-qur'an services to intrapartum patients to reduce labor pain levels.